Turtle, Water, and Silicon: Storyworking Indigenous Digital Methodologies - Cindy Tekobbe (Social Media + Society)
The author of this article contends that current digital research methodologies tend to extract and commodify knowledge in ways that can replicate social, cultural, racial, economic, and global inequities. This article presents an Indigenous approach to digital methodology, including examples of posts to Facebook, Instagram, and Bluesky, as well as algorithmic search results. Finally, the author discusses new opportunities within Indigenous methodologies as approaches for performing more inclusive digital research beyond settler colonial research paradigms.